2012
DOI: 10.1094/pdis-09-11-0789
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Blight of Taro (Colocasia esculenta) Caused by Phytophthora colocasiae in Ghana

Abstract: Taro (Colocasia esculenta (L.) Schott) is an important food crop cultivated for its edible tubers in Ghana. In May 2009, outbreaks of a destructive leaf disease were observed on several taro farms in the Atiwa, East-Akim, Fanteakwa, West-Akim, and New Juaben districts of the Eastern Region of Ghana. Symptoms began on leaves as small, brown, water-soaked lesions that enlarged and coalesced into large lesions with yellow exudate, ultimately leading to the defoliation and death of plants. Symptoms were suggestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…There is concern for food security and social unrest. The disease has spread rapidly to other countries in West Africa, including Nigeria and Ghana [17,18]. While it is too early to assess the impact of TLB on these countries, experience tells us that the disease has a potential to create a devastating cascade effect: reduction in food and household incomes, increased poverty and even starvation.…”
Section: History Of Taro Leaf Blight Epidemics and Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is concern for food security and social unrest. The disease has spread rapidly to other countries in West Africa, including Nigeria and Ghana [17,18]. While it is too early to assess the impact of TLB on these countries, experience tells us that the disease has a potential to create a devastating cascade effect: reduction in food and household incomes, increased poverty and even starvation.…”
Section: History Of Taro Leaf Blight Epidemics and Impactsmentioning
confidence: 99%
“…The Oomycete is now widely distributed geographically over almost all continents including Asia (Bangladesh, Brunei, China, India, Indonesia, Irian Jaya, Japan, Korea, Malaysia, Peninsular Malaysia, Myanmar, Nepal, Pakistan, Philippines, Sri Lanka, Taiwan, Thailand), Africa (Cameroon, Equatorial Guinea, Ethiopia, Ghana, Nigeria, Seychelles), North America (USA), Central America and Caribbean (Brazil, Cuba, Dominican Republic, Puerto Rico, Trinidad and Tobago), South America (Argentina), Oceania (American Samoa, Guam, Northern Mariana Islands, Palau, Papua New Guinea, Samoa, Solomon Islands) [17,18,56,57]. Some of these reports have not been verified and need confirmation.…”
Section: Origin Dispersal and Distribution Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…With the recent TLB outbreak and spread in West Africa, in Nigeria, 37 the global leader in taro production, and Ghana, 38 also among the top five global producers, access to TLB-resistant germplasm became vital. However, introducing new allelic diversity of taro globally is not only relevant for TLB resistance breeding but also for better adaptation to abiotic stresses exacerbated by climate change.…”
Section: Fighting Tlb Disease In Samoa and At Global Level Through Nementioning
confidence: 99%
“…after release and size of the cyst was 9.7 µm to 19.5 µm in diameter. Omane et al, (2012) reported morphological characters of P. colocasiae isolates of taro from Ghana. Sporangia were ovoid, hyaline, papillate, caduceus, 30 to 60 µm × 17 to 28 µm, and pedicels were 3.5 µm to 10 µm long.…”
Section: Zoosporesmentioning
confidence: 99%